INTERNATIONAL COOPERATION IN THE STUDY OF THE RUSSIAN ÉMIGRÉ EGO-DOCUMENTS - A. N. Kravtsov (Science and Innovation Center Publishing House, 2014)
The article will provide an overview of current state of international cooperation in Russian émigré ego-documentary scientific study. The conception of ego-documentary includes memories, memoirs, biographies, autobiographies, letters and diaries, and makes reference to the European philological and historical science in the beginning, and gradually accepted by the Russian scientific community. Theoretical base in studying the memoirs was developed in Soviet era. But practical study of ego-documentary was in suspended status there. It is so often that memoirs, and even biographies and autobiographies were biased on committed political nature. In post-Soviet era the reunion of Russian metropolis and émigré literature happened. Interest in the study and analysis of Russian émigré heritage is increasing year by year. At first instance it was dealt with the recognized Russian émigré literature masters, but then the range of scientific research began to cover the “second level” authors, periodicals (serials) publications, and single work authors. However the shortage of the publications exists. We need in the international cooperation between libraries and scientific centres especially in current digital era. Some examples of the cooperation are successful. It is worth to mention the dissertations, conferences and serials research workflow is increasing last years. So the interest is sustainable and has to be supported on the international level.